Electrode microstructure design to improve effective utilization of Fe-N/C catalysts towards oxygen reduction reaction process - Peng, Qin; Yang, Yang; Xu, Haokai; Schilling, Monja; Shah, Akeel; Zeis, Roswitha; Sui, Pang Chieh; Zhu, Xun; Li, Jun; Liao, Qiang (Chemical Engineering Journal, 2024)
Fe-N/C materials have shown intrinsic activities comparable to Pt/C catalysts for oxygen reduction reaction on rotating ring-disk electrodes (RRDE). However, due to the insufficient three-phase interfaces (TPIs) and high oxygen transport resistance (RT), the high intrinsic activity cannot be sufficiently utilized in electrodes, resulting in a gap between the intrinsic catalytic activity on RRDE and the performance in devices. To expand the TPIs and promote oxygen transport, a novel electrode with a transition layer structure is proposed to disperse the active sites. The dispersion degree of active sites is optimized by tuning the solid–liquid interfacial energy between the ink solvent and the substrate. A high electrochemical active area of 1264 cm2 and a low RT of 2.0 s cm−1 are achieved for the electrode prepared by an alcohol-rich ink. The simulation and experimental results demonstrate that the microstructure can benefit the extension of TPIs and facilitate oxygen transport in the air cathode, ultimately achieving efficient utilization of catalytic activities. A maximum power density of 35.4 mW cm−2 is achieved in a membrane-less direct formate fuel cell, surpassing most congeneric devices. Our approach clarifies the relationship between TPI construction, mass transport, and electrode microstructure, which successfully exploits the intrinsic activity on air cathodes and improves the power generation ability.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Catalyst ink regulation; Fe-N/C catalysts; Microstructure design; Oxygen transport resistance; Three-phase interface